School Readiness in India Perspective, Initiatives, Practice and Approaches - Chandra, Reetu (JOURNAL OF INDIAN EDUCATION, 2017)
School readiness over the last few decades is being globally treated as a significant component of Early Childhood Education (ECE). In India, it has set up its roots, starting from pledges in government documents, development and implementation of school readiness programmes, development of school readiness indicators, early learning indicators, school readiness assessment instruments and promoting researches in the area. This paper is a description of literature and research studies on school readiness in the global and the Indian context with an aim to explain the different perspectives in its understandings. It begins by tracing the development of school readiness concept, presenting the Indian scenario, reporting the ground reality, discussing the initiatives undertaken by the Government of India and suggesting approaches to ensure school readiness among children. Evidences from the literature and studies reveal that India has to go strategically, starting from ensuring the quality of pre-primary education for all children, providing early intervention, addressing diversity of children’s background and their experiences as well as development and use of appropriate assessment of school readiness of children.